Fabrication of CuSiC composite by powder metallurgy route - A. R. , Fatimah Azreen; Sutjipto, Agus Geter Edy; Adesta, Erry Yulian Triblas (Trans Tech Publications Ltd., Switzerland, 2011)
Copper-based composite now is a potential material for various applications, while powder metallurgy processing technique is an alternative for high temperature processing materials and net shape component. In this research, Cu-based composite containing 10-50 vol% SiC fibers was fabricated by employing the powder metallurgy route. The mixtures of SiC fibers and Cu particles were blended in a ball milling machine with the addition of ethanol at 150rpm. Then, the mixtures were uniaxially compacted into a ɸ13.5mm cylindrical pallet and followed by sintering in vacuum furnace from 800-950°C for 4 hours. The density of the composite decrease with increasing SiCf and density as high as 87% for 10vol% SiCf/Cu matrix sintered at 800°C had been achieved. The Vickers hardness of 774MPa also had been achieved for 10vol% SiCf/Cu matrix but sintered at 900°C.